Mecanismos antiulcerogênicos das fases clorofórmica e acetato de etila obtidas das partes aéreas de Praxelis clematidea (Griseb.) R. M. King & H. Robinson (Asteraceae) - Falcão, Heloina de Sousa (2011)
Praxelis clematidea (Griseb.) R. M. King & H. Robinson (Asteraceae) is a native herb to South America. The chloroformic phase from aerial parts of P. clematidea (CHCl3P-Pc) has hydroxylated and methoxylated flavones and it has shown gastroprotective activity. The ethyl acetate phase (AcOEtP-Pc) has hydroxylated flavonoids. So the gastroprotective activity of AcOEtP-Pc, the antiulcer mechanisms of CHCl3P-Pc and AcOEtP-Pc and the effects on duodenal ulcer, inflammation and gastrointestinal motility were investigated. The AcOEtP-Pc (62.5, 125 and 250 mg/kg, p.o.) protected gastric mucosa injuries by ethanol, stress and non steroidal anti-inflammatory in Wistar rats and male Swiss mice. The best dose of AcOEtP-Pc (62.5 mg/kg) did not alter biochemistry parameters of gastric juice by pylorus ligation model. The CHCl3P-Pc (125 mg/kg) and AcOEtP-Pc (62.5 mg/kg) prevented duodenal ulcer induced by hydrochloride cysteamine. The AcOEtP-Pc increased the amount of sticky mucus and depended of sulfhydryl compounds to gastric protection, while did not depend of NO. The CHCl3P-Pc and AcOEtP-Pc maintained the level of PGE2. These phases prevented gastric injuries induced by ischemia-reperfusion by decreasing LPO and activity of MPO, while they failed to maintain the activity of antioxidant enzymes such as SOD, GPx and GR, and GSH level. The CHCl3P-Pc and AcOEtP-Pc did not prevent the plasma extravasation when it evaluated by acetic acid induced vascular permeability model and paw edema induced by carrageenan, but they decreased the total number of peritoneal leukocytes after peritonitis induced by carrageenan. In this model, the AcOEtP-Pc reduced levels of cytokines TNF-α and IL-1β, while CHCl3P-Pc reduced TNF-α and increased IL-1β. The phases healed the chronic gastric ulcer induced by acetic acid after 15 days of treatment. In this model, there were re-structuring of the mucosa in ulcerated area (HE), increase of mucus secretion (PAS) and vasculature, as well as maintenance of cell proliferation after morphological and immunohistochemistry analysis. They have maintained expression of EGF and COX-2 after performing the technique of Western blot. The CHCl3P-Pc and AcOEtP-Pc did not also alter body weight, consumption of water and food, weight of vital organs, and hematological and biochemical parameters. The AcOEtP-Pc (62.5, 125 and 250 mg/kg) did not alter gastrointestinal motility when it was evaluated by gastric emptying, motility of small intestine and motility of colon by castor oil induced diarrhea, while the CHCl3P-Pc (125, 250 and 500 mg/kg) delayed the gastrointestinal motility. Therefore, the CHCl3P-Pc and AcOEtP-Pc are gastroduodenal protective and healing to develop cytoprotective, antioxidant and anti-inflammatory mechanisms and regulate the gastrointestinal motility.